Empathy philosophical and psychological perspectives - Coplan, Amy.; Goldie, Peter (Oxford : Oxford University Press, 2011)
In this interdisciplinary investigation of empathy leading researchers from philosophy and psychology explore the its role in our capacity to understand other people and predict what they think, feel, and do; the part it plays in our ethical responses to others; and its importance to our appreciation of art and fiction.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes index.
Keywords: Empathy